'A Summerhill in Scotland'? Experiences of freedom and community at Kilquhanity School (1940–1996). Issue 6 (26th November 2022) - Charkin, Emily
Abstract: In 1940, John and Morag Aitkenhead set up Kilquhanity School in rural Galloway, inspired by the writings of A.S. Neill and the practices at Summerhill School. In 1962, Aitkenhead wrote that he had swallowed 'hook, line and sinker' Neill's theories and that 'but for him and his example, there could never have been this free school in Scotland'. Historians and commentators have tended to share his view, for example, describing Aitkenhead as a 'disciple' of Neill and Kilquhanity as an 'approximate' of Summerhill with its weekly meeting, informality of relations between adults and children and a valuing of freedom and happiness over academic achievement. However, this article, drawing on primary research with ex-pupils and staff, uncovers significant differences of philosophy and practice between the two schools, particularly in relation to pupils' contribution to the Kilquhanity School community through the daily practice of 'useful work'. These differences raise questions about the positioning of Kilquhanity as simply a less well-known and less radical 'Summerhill in Scotland' and expose an often neglected fault line within the progressive and radical movements with which both schools are associated.